Word Order Irregularities and Sentence Patterns in Master Yoda's Speech - Dančová, Markéta (Univerzita Pardubice, 2017)
This bachelor thesis deals with word order irregularities and sentence patterns in Master Yoda's speech and it is divided into a theoretical part and a practical part. The theoretical part describes the unmarked word order and provides explanation of commonly used structures which differ from the regular English word order, namely fronting, inversion, and ellipsis. The structures and their subcategories are described in detail and contexts in which it is possible and common to use them are shown on example sentences. Based on the theory, the practical part describes the patterns used in Master Yoda's speech and gives explanation on how and when these patterns are used.
Nepravidelnosti slovosledu a větné vzorce v řeči mistra Yody
Keywords: inversion; fronting; ellipsis; spoken language; Star Wars; Master Yoda; inverze; prepozice; elipsa; mluvená řeč; Star Wars; Mistr Yoda